HUBUNGAN DERAJAT DISPNEA TERHADAP KUALITAS HIDUP PENDERITA TUBERKULOSIS PARU - Elza " Oktalista; Siti " Rahmalia; Veny " Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Pulmonary tuberculosis is an infectious disease directly caused by mycobacterium tuberculosis. The aim of this research is to identify the correlation between grade of dyspnea and quality of life in pulmonary tuberculosis patient in Poli Paru Arifin Achmad Hospital. The research isdesign by descriptive correlation with retrospective.The sample of this researchis 66 respondents that is select based on inclusion criteria. The data is collect by using questionnaire. The questionnaire is adopt from Modified Medical Research Council (MMRC) to measure grade of dyspnea and WHOQOL-BREF to mesure quality of life. The questionnaire for quality of life is tasted the validity of the result (r = 0.497-0.785) and reliability test with Cronbach Alpha’s = 0.947. The data is analyze by ANOVA test and the result showed the higher grade of dyspnea, the lower quality of life and there is correlation between garde of dyspnea and quality of life in pulmonary tuberculosis patient withdegree p value (0.004) <α(0.05).Based on the results of this research, it is expected for nurses to provide health education about breathing exercise to increase quality of life in pulmonary tuberculosis patient. Keyword: Grade of dyspnea, pulmonarytuberculosis, quality of life